(untitled) (Praxis Educativa, 2012)
The present meaning of assessment has been historically constructed. This research work starts analyzing the origins of the testing system in high schools of the national educational system at the beginning of the XX Century by focusing on the first local antecedent in the National Territory of what today is the Province of La Pampa: "Julio Argentino Roca Normal School" of Santa Rosa de Toay (founded in 1909), In its teachers’ as well as in the ministry’s legal documents, the "Normal" School provides the necessary elements to analyze its constitution as the pre-history of assessment. In this sense, the present, trace continuities, realize for what and to whom tests are useful, to what kind of power systems they are linked , how they make our present-day conditions possible: the genesis of exams; what is being assessed; who are considered to be the good students; promotion vs. assessment; oral and written test; effort, will, duty. In short, the role of school playing one of its most powerful social magistracies: condemning or consecrating school subjects.